European Ai-Policy Space - R. S. Vykhodets (Евразийская интеграция: экономика, право, политика, 2021)
Artificial Intelligence (AI) is one of the central technologies of the fourth industrial revolution. A significant part of the production of surplus value in the XXI century is associated with the mastery and widespread introduction of technologies, which contributes to the consolidation of technological competition as an object of state policy and an important component of international relations. The European Union today occupies a leading position in the field of technology development and Since 2018 the EU is in the process of forming a unified strategy in the field of AI, the directions, principles and approaches of which are the main subject of this article.The study is primarily based on the analysis of official documents included in the EU Strategy on AI: White Paper, Coordination Plan, Proposal for a Regulation establishing harmonized rules for artificial intelligence in the EU, documents of the expert groups of the European Commission, etc. The analysis of the EU policy to promote its own vision and approaches at the international level is based on theoretical models of the concept of “soft power” and the neo-institutional approach.Against the backdrop of fierce global technological competition, the EU was one of the first in the world to form a holistic strategy for the development of AI technologies. This makes it possible not only to strengthen its own position as a world leader in the field of innovative technologies, but also to significantly expand the intra-European and international integration agenda, as well as to supplement the European arsenal of soft power with tools to promote its own norms, standards and ethical principles of AI development at the global level.The key directions of the EU AI Policy are identified and disclosed. These include investments in technologies, creating conditions for their development, promoting development and implementation, creating an educational and regulatory environment, promoting the European vision of AI technology development at the international level. The authors considered key mechanisms of political regulation at the EU level, forms of interaction between stakeholders, approaches to promoting common principles in the field of ethics and security of AI technologies within the EU and at the international level.